1990
DOI: 10.1161/01.cir.81.3.970
|View full text |Cite
|
Sign up to set email alerts
|

Renal and hemodynamic effects of intravenous fenoldopam versus nitroprusside in severe hypertension.

Abstract: sure in hypertensive emergencies, nitroprusside is still considered the drug of choice because of its rapid onset of action, short serum half-life, and long history of efficacy.6 The major disadvantage of nitroprusside is the conversion to its very toxic metabolites, cyanide and thiocyanate. This problem is often manageable by limiting the dose and duration of infusion. Despite shortterm, low-dose administration, however, nitroprusside has been associated with deterioration in renal,2-5 cerebral,7-9 and cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
4

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 32 publications
1
56
0
4
Order By: Relevance
“…Fifteen RCTs (869 patients) were found that satisfied the inclusion criteria [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ( Table 2). Two trials were placebo controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen RCTs (869 patients) were found that satisfied the inclusion criteria [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ( Table 2). Two trials were placebo controlled.…”
Section: Resultsmentioning
confidence: 99%
“…106 A comparative study of fenoldopam with nitroprusside in patients with hypertensive crisis revealed that while both of these compounds caused a prompt lowering of blood pressure, the additional beneficial effect seen with fenoldopam was that it promoted natriuresis and diuresis in these patients. 107 Because RBF was not measured in this study, it is not clear whether natriuretic response was secondary due to an increase in RBF or whether it resulted from the direct tubular action of fenoldopam on D 1 -like dopamine receptors. It is reported that activation of D 1 -like receptors located on the juxtaglomerular cells causes an increase in renin release, 63 and we have shown in animal experiments that the natriuretic and diuretic effect of fenoldopam is markedly potentiated by pretreatment with angiotensin-converting enzyme inhibitors and losartan.…”
mentioning
confidence: 91%
“…Ironically despite decreasing the blood pressure, it increases the renal perfusion [22][23][24]. In several studies comparing fenoldopam to other anti hypertensive agents in hypertensive emergencies, improved creatinine clearance was observed [25][26][27]. Therefore, this could be a useful drug in patients with hypertensive emergencies associated with acute renal failure.…”
Section: Fenoldopammentioning
confidence: 99%
“…Nitroprusside is often used; however it has increased risk of cyanide toxicity in patients with renal failure. Fenoldopam-the dopamine 1 agonist, has been shown to improve natriuresis, diuresis and creatinine clearance compared to nitroprusside in a few studies and is currently preferred over nitroprusside in patients with renal failure [25][26][27].…”
Section: Acute Kidney Injurymentioning
confidence: 99%